Community empowerment psychosocial support for disaster survival children in Adonara - Epifania M. Ladapasea; Sitti Anggrainia; Agustinus Rudi Yantoa; Yosep Don Bosko Baraa; Yuliana Yustanti Witaka; Yenita Lusia Welina; Yohana Yunita Owona (Peneliti Teknologi Teknik Indonesia, 2021)
The Seroja cyclone disaster that occurred in East Adonara, East Flores, left deep wounds for the community, the families of the victims who died, lost property, and lost their homes and relatives. This certainly causes severe psychological disturbances for family members, especially for children who have survived the disaster. The results of the assessment of the condition of the children in the Nelelamadiken Village area, East Adonara are very concerning. These child survivors seem to have received less serious attention from their parents and the local government. It should be noted that the banjirbandang disaster is not the main factor causing trauma and psychological injuries to children in the area, but it is only a reinforcing factor for the deepening of the wounds felt by children who survived the disaster. For this reason, there is a need for psychosocial support in overcoming the psychological vulnerability of the survivors. Psychosocial support is a process to facilitate the development of well-being in a person by using the resources that exist within himself and also the resources that exist in his community or social environment. This psychosocial support aims to minimize the physical, psychological and social impacts caused by disasters or crisis situations. Psychosocial support is carried out for 14 days, namely three days of conducting an assessment and ten days of carrying out psychosocial support programs according to the needs of children who have survived the disaster. The psychosocial support program for 14 days showed a significant change in the behavior of the children who survived the disaster.